Evaluation of the Child With Gullian-Barre Syndrome in Accordance with the Theory of Technological Competence - Dilek Zengin; Yasemin Yıldırım; Çiçek Fadıloğlu; Fisun Şenuzun Aykar (Galenos Yayinevi, 2020)
Each of the theories or conceptual model represents a unique way directing nursing practice. Theories contribute to explain the meaning of scientific results and the emergence of new researches, as well as the use of information in a systematic way and the development and professionalization of the nursing profession. In this article, a 4-year-old male patient with Gullian-Barre syndrome, whose illness started with acute symptoms and progressed rapidly and who survived in a technologically dependent situation, was included in the nursing process with theory of technological competence.